(3GdEfUGas - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd ZQVg Hbhdg Ef cGfJ GdLhGgQ aGSOI aGdcd aGSO Cf jKHJ GdLhGgQ GdaGQb ddeGOI s
(3BNQgG (B:s
(3de jcf GdhLhO eTJedkG Ydi LejY CfMGA GdhLhO Gdeecf ade jLH Cf jba GdhLhO bHd GdhUhd Edi NjQ Gdchf hGdaSGO GfbVi HMeO Gddg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3TQM MQa GddGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B183s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MceI hadSaI (B216) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs